Nicotinic Receptors and the Treatment of Attentional and Cognitive Deficits in Neuropsychiatric Disorders: Focus on the α7 Nicotinic Acetylcholine Receptor as a Promising Drug Target for Schizophrenia - Chiamulera, Christian; Fumagalli, Guido (Central Nervous System Agents in Medicinal Chemistry, 2007)
A large body of evidence shows that α7 nicotinic acetylcholine receptor (nAChR) is an important mechanism underlying attentional and cognitive deficits in schizophrenia. Several compounds acting as activators of α7 nAChRs have been identified and investigated for a potential therapeutic application. However, considering the complexity of neuropsychiatric disorders and the difficulty to meet an ideal product profile for drug discovery in the field, there is the need to define empirical product profiles from available data for the major α7 activators. Two classes of compounds are described, partial/full α7 agonists and α7 positive allosteric modulators (PAMs). Their critical pharmacological features are analysed by focussing on type of activity/selectivity at α7 nAChR, action in vivo in laboratory animal models, desired clinical activity, pharmacokinetics (PK)/dosing and safety/tolerability issues. Although the characterization of type of efficacy in vitro succeeded in the extrapolation to animal models and to patients, more efforts are needed to improve selectivity, PK/dosing and safety/tolerability features for α7 agonists. Such as limitations have not been seen for α7 PAMs, so that this class may offer a potential back-up strategy for α7 activators development. The empirical profiles proposed here might give pragmatical indications for the development and the optimization of α7 activators. Few issues need to be further optimized, i), in the clinic, mostly PK profiling, and, ii), at a preclinical level, downstream α7 receptors mechanisms involved in cognitive deficits. A successfully translation of α7 activators research for the treatment of schizophrenic patients will rely on a continuous clinical/preclinical cross-talk approach.
Keywords: cognition